The Five Sexes, Revisited: The Varieties of Sex Will Test the Medical Values and Social Norms: Петте пола, повторно: Вариететите на полот ќе ги тестираат медицинските вредности и општествените норми - Fausto-Sterling, Anne; Trajanoski, Žarko (Identities: Journal for Politics, Gender and Culture, 2004)
Author(s): Anne Fausto-Sterling | Ен Фаусто-Стерлинг Title (English): The Five Sexes, Revisited: The Varieties of Sex Will Test the Medical Values and Social Norms Title (Macedonian): Петте пола, повторно: Вариететите на полот ќе ги тестираат медицинските вредности и општествените норми Translated by (English to Macedonian): Žarko Trajanoski | Жарко Трајаноски Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 3, No. 1 (Summer 2004) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 207-221 Page Count: 14 Citation (English): Anne Fausto-Sterling, “The Five Sexes, Revisited: The Varieties of Sex Will Test the Medical Values and Social Norms,” Identities: Journal for Politics, Gender and Culture, Vol. 3, No. 1 (Summer 2004): 207-221. Citation (Macedonian): Ен Фаусто-Стерлинг, „Петте пола, повторно: Вариететите на полот ќе ги тестираат медицинските вредности и општествените норми“, превод од англиски Жарко Трајаноски, Идентитети: списание за политика, род и култура, т. 3, бр. 1 (лето 2004): 207-221.